Professional Learning Experience of Pre-service PE Teachers during Teaching Practice: 體育師訓生於學校實習的專業學習經歷 - LI, Chung (Asian Journal of Physical Education & Recreation, 2007)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. This paper is concerned with a qualitative study of how 15 pre-service PE teachers, who are taking the two-year full-time teacher training course, develop professionally in their second field experience. With the interpretive research paradigm as conceptual framework, data were collected through interviewing and writing of reflective journals. Groups of pre-service PE teachers were found possessing different professional learning experiences concerning their conceptions and socializing strategies. Their professional conceptions included "educating pupils to learn", "seeing PE as catharsis, discipline and having fun". Their socializing strategies composed of finding means to improve teaching, and adopt social tactics for managing pupils and defensive attitude for handling crisis. The study provides an understanding of pre-service PE teachers in the Hong Kong Institute of Education and their learning-to-teach processes. The findings serve as the backdrop for recommending possible pedagogical changes for facilitating desirable professional development of pre-service PE teachers. 本研究目的是利用詮釋理念，透過會談及反思報吿所搜集的資料，探討十五位體育師訓學員於第二次學校實習的經歷。研究結果顯示學員基於不同的意向及經歷而對體育的敎學有著不同的理念，其中包括視之為促進學生學習、減輕壓力、訓練紀律和獲取歡樂等工具。他們的職化策略則包括改善敎學方法、運用社交手段以管理學生及採取防禦性的態度以應付危機。研究結果有助加深了解這些準體育敎師的專業發展，期望能對體育師資培訓課程帶來實際的啟示。